Förster resonance energy transfer in fluorophore labeled poly(2-ethyl-2-oxazoline)s. Issue 40 (1st October 2020) - Merckx, Ronald; Swift, Thomas; Rees, Ryan; Van Guyse, Joachim F. R.; Schoolaert, Ella; De Clerck, Karen; Ottevaere, Heidi; Thienpont, Hugo; Jerca, Valentin Victor; Hoogenboom, Richard
Abstract : A well-defined FRET system based on heterotelechelic poly(2-ethyl-2-oxazoline) containing pyrene and coumarin 343 was successfully used as fluorescent probe for temperature sensing and processed into fibres and films showing excellent FRET efficiency. Abstract : Dye-functionalized polymers have been extensively studied to understand polymer chain dynamics, intra or inter-molecular association and conformational changes as well as in practical applications such as signal amplification in diagnostic tests and light-harvesting antennas. In this work, the Förster resonance energy transfer (FRET) of dye-functionalized poly(2-ethyl-2-oxazoline) (PEtOx) was studied to evaluate the effect of dye positioning and polymer chain length on the FRET efficiency. Therefore, both α (initiating terminus)- or ω (terminal chain end)-fluorophore single labeled and dual α, ω-fluorescent dye labeled PEtOx were prepared via cationic ring opening polymerization (CROP) using 1-(bromomethyl)pyrene as the initiator and/or 1-pyrenebutyric acid or coumarin 343 as the terminating agent, yielding well-defined PEtOx with high labeling efficiency (over 91%). Fluorescence studies revealed that intramolecular FRET is most efficient for heterotelechelic PEtOx containing both pyrene and coumarin 343 fluorophores as chain ends, as expected. A strong dependence of the energy transfer on the chain length was found for these dual labeled polymers. The polymers were tested in both dilute organic (chloroform) and aqueous media revealing a higher FRET efficiency in water due to the enhanced emissive properties of pyrene. The application of dual labeled polymers as fluorescent probes for temperature sensing was demonstrated based on the lower critical solution temperature behavior of the PEtOx. Furthermore, these polymers could be successfully processed into fibers and thin films. Importantly, the fluorescence properties were retained in the solid state without decreasing the FRET efficiency, thus opening future possibilities for application of these materials in solar cells and/or sensors.